The Relational Ethics of Cultural Safety, Rights, and Desire: Reflections on Doing Community-Engaged Research with Migrant Families in Indonesia - Ball, Jessica; Beazley, Harriot (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
A study of birth registration decision making by Indonesian parents involved in transnational migration is discussed with reference to the authors’ long-standing use of an approach centred on the relational ethics of cultural safety, rights, and desire in community-engaged research. Ethical dilemmas encountered in obtaining informed consent and conducting the research, resulting from social hierarchies, social protocols, and socio-emotional considerations, illustrated limited, often mismatched perspectives on consent, privacy, and protection on the parts of research gatekeepers in minority and majority contexts. The article discusses “in-the-moment” adaptations to planned data collection procedures. These adaptations were guided by relational ethics aimed at ensuring, not only meaningful data, but consent, authenticity, socioemotional and cultural safety, a legacy of good relations with village leaders, and beneficial outcomes for community members.